THE MEASUREMENT OF BRAND EQUITY TOWARD DECISION BUYING PROCES ON WATER MINERAL - Ramli Ramdani; Bonifasius MH. Nainggolan (LPPM Universitas Asa Indonesia, 2015)
Business is the World when competition is a real, many kind of strategy is a must for marketing a product, one sample Brand Product, Because sometime the big name of a brand more many people know than the product name, The purpose of this research is to knowing of brand equity element effect for buying decision, And the subject is people in RT 3 RW 1 Harjasari.Bogor, when using quantitative analysis with nonprobability sampling, the result is brand equity for simultaneous have a strong and real effect to buying decision, but for partial have a varies result, for brand awareness and brand association have a real effect but weak, for brand loyalty have a real effect and middling, and for perceive quality have a not real effect and weak, Because of this for build the brand equity must looking all aspect to make a strong and real effect to buying decision.